The Effect of Autologous Platelet-Rich Gel on the Dynamic Changes of the Matrix Metalloproteinase-2 and Tissue Inhibitor of Metalloproteinase-2 Expression in the Diabetic Chronic Refractory Cutaneous Ulcers - Lan Li; Dawei Chen; Chun Wang; Guanjian Liu; Xingwu Ran (Journal of Diabetes Research)
Aim. To investigate the dynamic changes on the expression of matrix metalloproteinases (MMPs) and tissue inhibitor of metalloproteinases (TIMPs) in the diabetic chronic refractory cutaneous ulcers after the autologous platelet-rich gel (APG) treatment. Methods. The study was developed at the Diabetic Foot Care Centre, West China Hospital. The granulation tissues from the target wounds were taken before and within 15 days after APG application. The expression of MMP-2 and TIMP-2 as well as transforming growth factor-β1 (TGF-β1) in the granulation tissue was detected by q TR-PCR and IHC. The relationship between the expression level of MMP-2 and TIMP-2 and their ratio and that of TGF-β1 was analyzed. Results. The expression of MMP-2 (P < 0.05) was suppressed, and the expression of TIMP-2 (P < 0.05) was promoted, while the ratio of MMP-2/TIMP-2 (P < 0.05) was decreased after APG treatments. The expression of TGF-β1 had negative correlation with the ratio of MMP-2/TIMP-2 (P < 0.05) and positive correlation with the expression of TIMP-2 (P < 0.05). Conclusions. APG treatment may suppress the expression of MMP-2, promoting that of the TIMP-2 in the diabetic chronic refractory cutaneous wounds. TGF-β1 may be related to these effects.